Development of non-derivatizing hydrate salt pre-treatment solvent for pre-treatment and fractionation of corn cob. Issue 1 (1st January 2021) - Ejekwu, Olayile; Ayeni, Augustine Omoniyi; Sadare, Olawumi; Daramola, Michael Olawale
Abstract: Major concern in beneficiating lignocellulose is overcoming biomass recalcitrance through pre-treatment. Molten hydrate salts (MHS) is a green solvent with ability to swell and dissolve cellulose and biomass in a non-derivatizing way. Over the last decade, MHSs have been used for isolated cellulose dissolution, however very few studies have been reported on their effectiveness in pre-treating lignocellulosic biomass. Therefore, effectiveness of their application as solvent for pre-treating and fractionating corn cob is presented in this article. In this study, seven molten hydrate salt pre-treatment solvent systems such as unary, binary and ternary mixtures of ZnCl2.4H2O, LiClO4.3H2O and Urea were investigated for their ability to pre-treat and fractionate biomass. The pre-treatment experiments were carried out in a shaking incubator at 70°C for 60 minutes at a biomass: solvent ratio of 1:10. The surface chemistry of the biomass was checked before and after pre-treatment using Fourier Transform infrared spectroscopy. X-ray diffraction and scanning electron microscopy were employed to check the crystallinity and surface morphology of the biomass. Physicochemical analysis consistently indicated a disruption in the structure of corncob due to removal of lignin and hemicellulose during the pre-treatment process. Additionally, results showed a decrease in crystallinity and a change in surface morphology after the pre-treatment using all the seven solvent systems (MHS solvents). The use of ZnCl2.4H2O/ Urea solvent displayed 100% recovery of cellulose, 42% recovery of hemicellulose and 44% recovery of lignin from the corn-cob when compared to the performance of the other proposed solvent systems in this study.